Transportation then and now - Nelson, Robin, 1971- (Minneapolis : Lerner, 2003)
Presents a brief look at how transportation has changed over the years.
Includes index.
School Library Journal.
School Library Journal, December 2003.
3.0.
3.0
K-3
Keywords: Transportation -- United States -- History -- Juvenile literature; Transportation -- History; Transportation -- History